The Importance of an Education in Humanities for Employment: Perception of Graduates from a Peruvian University - Cervera Vallejos, Mirtha Flor (2019)
Knowledge of the Humanities has become undervalued as part of career preparation given the predominance of Science and Technology. However, it is acknowledged that higher learning institutions must also prepare future professionals comprehensively, as required by society. This article reveals the results of qualitative research with focal groups gathered to discuss their perceptions about graduates from a Peruvian University the need of education in the humanities to future graduates. The semi-structured interviews were conducted with the four focal groups. The groups were composed o 32 graduates from the universities involved in the study. Sampling was intentional and with a snow ball effect until saturation was obtained. Data was processed based on analysis of each participant´s discourse which was coded to protect their identity. It was concluded that teaching about the Humanities fosters personal social growth, particularly among graduates who will one day join the work force.